(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective of the study was to review knowledge, practice of hand washing among health staff and some related factors in developing countries during 2011-2020. Sduty design was a scoping review. The number of reviewed articles were 37 including international and Vietnam papers. Results shown that the knowledge in hand washing among healt staff was rather good (range 54-94.5%). Nurses was more frequently to have hand washing than that of doctors. Factors such as difficult to access to hand washing facilities, overload of patients and works, lack of soap and alcol fluid. Contributed to the reduction of hand washing. Other factors such as training, availability and access to hygiene facilities were to increase the rate of hand washing among health staff. To increase hand washing among health staff, these factors should be considered in health facilities.